Сопоставительный анализ детонационных наноалмазов, полученных в различных условиях - Богатырева, Г.П.; Долматов, В.Ю.; Веретенникова, М.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
In the work classical for diamonds analysis results used for detonation nanodiamonds
(DND) are presented. It is shown that for just identification the development of additional analysis
methods is necessary. The present analytical methods are under-informative.
DND obtained at detonation of a TNT-RDX (40/60) charge in aqueous solution of urea is
demonstrated to have the best quality among the investigated samples.